Knowledge, attitude, and practice toward COVID-19 in Trinidad and Tobago - Azad Mohammed; Vrijesh Tripathi; Delezia Singh; Lauren Ali; Ruth Mohan; Sedique Graham; Saraswatie Sankar; Naresh Nandram (Journal of Social Behavior and Community Health, 2021)
Background: Severe Acute Respiratory Syndrome Coronavirus 2 (COVID-19) has affected over 250 million people globally and resulted in over 5 million deaths since it was first reported in November 2019. Methods: A cross-sectional study was conducted online from July to September 2020 among nationals and permanent residents of Trinidad and Tobago (N = 812). The related questionnaire consisted of demographic characteristics, 11 items on knowledge, 11 items on attitude and 7 items on practice and experience. Domain scores were derived for each component (K, A and P) and independent t-tests and one-way ANOVA were used to compare differences in scores within demographic categories. Results: The population possessed a high level of knowledge about COVID-19(0.85 ± 0.09). Attitude scores (0.54 ± 0.07) were influenced by factors such as sex, age, occupation, level of education and area of residence. Significant relationships (P<0.05) were found between demographic categories of sex, age, profession, education, geographical region and the mean domain scores. Conclusion: There was overall high level of knowledge and good practices in response to COVID-19 which suggests that the government's management approach was effective in providing information about COVID-19 and the safe practice needed to reduce spread of the virus.